2009
DOI: 10.1148/radiol.2513081330
|View full text |Cite
|
Sign up to set email alerts
|

Hypervascular Liver Tumors: Low Tube Voltage, High Tube Current Multidetector CT during Late Hepatic Arterial Phase for Detection—Initial Clinical Experience

Abstract: By substantially increasing the tumor-to-liver CNR, a low tube voltage, high tube current CT technique improves the conspicuity of malignant hypervascular liver tumors during the late hepatic arterial phase while significantly reducing patient radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(105 citation statements)
references
References 22 publications
4
97
4
Order By: Relevance
“…Image quality is not only a nonmeasurable entity, at least objectively, but it cannot even be precisely defined. Assessing image quality both objectively by noise and attenuation measurements 11,13,25 and subjectively by experienced radiologists blindly rating images with predefined scores is generally accepted. 11,13,16,18,25 The complex anatomy and wide variation of thickness and attenuation of the H&N region imply differences in noise levels and image quality; therefore, we chose representative anatomic levels similar to those described in a previous study, 18 instead of collectively judging all images.…”
Section: Discussionmentioning
confidence: 99%
“…Image quality is not only a nonmeasurable entity, at least objectively, but it cannot even be precisely defined. Assessing image quality both objectively by noise and attenuation measurements 11,13,25 and subjectively by experienced radiologists blindly rating images with predefined scores is generally accepted. 11,13,16,18,25 The complex anatomy and wide variation of thickness and attenuation of the H&N region imply differences in noise levels and image quality; therefore, we chose representative anatomic levels similar to those described in a previous study, 18 instead of collectively judging all images.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little attention has been paid to the potential for enhanced detection of hypervascular pathologies at dual energy CT [6], despite the predicted advantage of low kV imaging in phantom models [7,8]. Marin et al recently demonstrated, however, that low kV imaging results in increased conspicuity of hypervascular liver lesions [9]. Material characterization at hepatic CT may be beneficial if increased lesion detection or ability to quantitate fat or iron are realized.…”
Section: Introductionmentioning
confidence: 99%
“…Such lowkilovolt protocols are used in cerebral perfusion CT in the evaluation of patients with stroke 16 and in pediatric CT. 17 In phantom 18 as well as in clinical studies, it has been demonstrated that this technique can also be used in chest and abdominal imaging in adults. [19][20][21][22][23][24] Lower tube voltage in CTA results in higher noise levels on one hand, but the attenuation of iodine is increased 25,26 on the other hand. This relationship must be considered when trying to reduce radiation exposure by use of low-kilovolt scanning and to maintain image quality.…”
mentioning
confidence: 99%